Final 5-Year Study Results of DASISION: The Dasatinib Versus Imatinib Study in Treatment-Naïve Chronic Myeloid Leukemia Patients Trial - Cortes, JE (2016)
Purpose: We report the 5-year analysis from the phase III Dasatinib Versus Imatinib Study in Treatment-Naïve Chronic Myeloid Leukemia Patients (DASISION) trial, evaluating long-term efficacy and safety outcomes of patients with chronic myeloid leukemia (CML) in chronic phase (CP) treated with dasatinib or imatinib. Patients and methods: Patients with newly diagnosed CML-CP were randomly assigned to receive dasatinib 100 mg once daily (n = 259) or imatinib 400 mg once daily (n = 260). Results: At the time of study closure, 61% and 63% of dasatinib- and imatinib-treated patients remained on initial therapy, respectively. Cumulative rates of major molecular response and molecular responses with a 4.0- or 4.5-log reduction in BCR-ABL1 transcripts from baseline by 5 years remained statistically significantly higher for dasatinib compared with imatinib. Rates for progression-free and overall survival at 5 years remained high and similar across treatment arms. In patients who achieved BCR-ABL1 ≤ 10% at 3 months (dasatinib, 84%; imatinib, 64%), improvements in progression-free and overall survival and lower rates of transformation to accelerated/blast phase were reported compared with patients with BCR-ABL1 greater than 10% at 3 months. Transformation to accelerated/blast phase occurred in 5% and 7% of patients in the dasatinib and imatinib arms, respectively. Fifteen dasatinib-treated and 19 imatinib-treated patients had BCR-ABL1 mutations identified at discontinuation. There were no new or unexpected adverse events identified in either treatment arm, and pleural effusion was the only drug-related, nonhematologic adverse event reported more frequently with dasatinib (28% v 0.8% with imatinib). First occurrences of pleural effusion were reported with dasatinib, with the highest incidence in year 1. Arterial ischemic events were uncommon in both treatment arms. Conclusion: These final results from the DASISION trial continue to support dasatinib 100 mg once daily as a safe and effective first-line therapy for the long-term treatment of CML-CP.